Islamic Education Model in the Context of Sexual Bullying Prevention with a Sociolinguistic Approach - Maya Safitri; Hasniyati; Nia Wardhani; Muhammad Iqbal (Universitas Nahdlatul Ulama Surabaya, 2024)
This research aims to develop an Islamic education model for preventing sexual bullying using a sociolinguistic approach. This approach analyzes language use and social interactions within Islamic education to understand and mitigate sexual bullying behavior. The main issue highlighted is the lack of understanding regarding the integration of sociolinguistic principles into these models. A qualitative research method was employed, involving 5 respondents from Islamic educational settings, 2 sociolinguistic experts, and 3 Islamic religious teachers. Data were collected through interviews, observations, and document analysis, with social integration theory applied in the data analysis. The findings indicate that educational models such as communication etiquette training, social skills development, the teaching of law and ethics, Islamic religious education, and shared responsibility learning play crucial roles in preventing sexual bullying. They support the formation of a positive social identity and strengthen interpersonal relationships. The uniqueness of this research lies in integrating sociolinguistic and Islamic approaches to address sensitive issues like sexual bullying. In conclusion, Islamic education models based on sociolinguistic principles have significant potential to reduce incidents of sexual violence in educational environments.